Soft Measurement and Calculations in Evolutionary Control of Continuous Multistage - В. V. Palyukh; A. N. Vetrov; I. A. Egereva (Informaciâ i Innovacii)
A mechanism for efficient management of the evolution of multi-stage production based on the use of soft measurements and calculations is considered. To reduce the sensitivity to noise interference and delays along dynamic channels between the input and output of continuous multistage production, a diagnostic system based on the analysis of the intervals of change in the values of diagnostic variables for a given time interval is proposed. The decision making system is based on the methods of the Dempster-Schafer theory. The process control architecture model is described as a multi-agent system in which agents interact with each other and with the center. Methods and tools for managing the evolution of multi-stage continuous processes are substantiated to improve efficiency and long-term sustainability throughout the entire life cycle by introducing innovative solutions.